1997
DOI: 10.1016/s0735-1097(97)00348-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Stent Placement: Utility in Lesions Difficult to Treat With Balloon Angioplasty

Abstract: Renal artery stenting is an effective treatment for renovascular hypertension, with a low angiographic restenosis rate. Stent placement appears to be a very attractive therapy in patients with lesions difficult to treat with balloon angioplasty such as renal aorto-ostial lesions and restenotic lesions, as well as after a suboptimal balloon angioplasty result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
1
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(118 citation statements)
references
References 24 publications
5
107
1
5
Order By: Relevance
“…Stenting can deal with these problems and previous studies have reported immediate success rates of 94-100%, residual diameter stenosis of less than 10% and 1 year restenotic rates of less than 25%. 8,9 Poorly controlled BP despite three antihypertensive drugs and a unilateral small kidney on ultrasound were clinical clues to the presence of a significant renovascular lesion in this patient. Further functional assessment was not performed.…”
Section: Case Reportmentioning
confidence: 80%
“…Stenting can deal with these problems and previous studies have reported immediate success rates of 94-100%, residual diameter stenosis of less than 10% and 1 year restenotic rates of less than 25%. 8,9 Poorly controlled BP despite three antihypertensive drugs and a unilateral small kidney on ultrasound were clinical clues to the presence of a significant renovascular lesion in this patient. Further functional assessment was not performed.…”
Section: Case Reportmentioning
confidence: 80%
“…Stenting cured hypertension in 0-16%, with improvement (mean reduction of half of one hypotensive drug) in around half of patients. 19,25,26 Even the modest improvement in blood pressure may be overestimated in these uncontrolled studies as recorded blood pressure in patients with RVH spontaneously falls with follow up. 28 Three prospective randomised controlled trials comparing PTRA +/− stenting have recently reported.…”
Section: Does Revascularisation Beneficially Affect Hypertension or Rmentioning
confidence: 97%
“…Several series report initial technical success of over 90% with less than 20% restenosis over 2 years. 5,19,[24][25][26] A clear benefit of revascularisation over medical management of atheromatous renovascular hypertension has not been demonstrated. Ramsay reviewed 10 uncontrolled series of PTRA for atheromatous RVH.…”
Section: Does Revascularisation Beneficially Affect Hypertension or Rmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] While restenosis occurs in > 50% of patients treated with percutaneous transluminal renal angioplasty, 9-11 restenosis rates of renal artery stents are only 10-25%. [2][3][4][5][6] As expected, the risk of renal artery stent restenosis is related to stent diameter, with larger stent diameters having lower rates of restenosis. Lederman et al demonstrated that renal stents with > 4.5 mm diameter had a 12% restenosis rate while renal stents of < 4.5 mm in diameter had restenosis rate of 21%.…”
Section: Case Reportmentioning
confidence: 99%
“…Renal artery stenting is the procedure of choice for treating atherosclerotic renal artery stenosis. [1][2][3][4][5][6][7][8] However, long-term benefits of renal artery stenting may be blunted by the development of stent restenosis, and the treatment of this condition is not well established, with limited therapeutic options. We present a case report of intravascular ultrasound-guided cutting balloon angioplasty (CBA) as a novel technique for the treatment of renal artery stent restenosis.…”
Section: Introductionmentioning
confidence: 99%